Penggunaan E-LKPD Berbasis HOTS Pada Pembelajaran Biologi Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMA - Dhea Forenza; Annisa Berliana; Revi Melda Restina; L.N Firdaus; Surtika, Surtika (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
21st-century learning emphasizes higher-order thinking skills (HOTS), particularly critical thinking. However, high school students’ critical thinking skills in biology learning tend to be relatively low due to the dominance of conventional teaching methods and limited instructional media. This study aims to examine the effectiveness of HOTS-based E-LKPD in improving students’ critical thinking skills and to determine the level of improvement. This study employed a meta-analysis method by analyzing 20 scientific articles published between 2020 and 2026. Data were obtained from selected research articles based on inclusion and exclusion criteria, and were analyzed using effect size (Hedges’g). The results showed that most effect size values were in the moderate to high categories, ranging from 0.45 to 2.10 (moderate to large effect). The highest values were found in the topic of growth and development, while topics such as cell division, respiratory system, and excretory system were in the moderate category. These findings indicate that the use of HOTS-based E-LKPD has a significant effect on improving students’ critical thinking skills. In conclusion, HOTS-based E-LKPD is effective in improving students’ critical thinking skills, although its effectiveness varies depending on the characteristics of the learning material.